The Influence of Competence and Teacher Character Values on Teacher Performance and Its Implications for Child Learning Outcomes (Case study at elementary schools in Bandung Regency) - Adhie Fasha Nurhadian; Farid Riadi; Vicky Achmad Zulfikar (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
This study aims to determine and examine teacher competence and character values' effect on teacher performance and its implications for children's learning outcomes in elementary schools in Cileunyi sub-district, Bandung regency. This research was conducted in Elementary Schools, Cileunyi District, Bandung Regency, with a sample of 93 teachers. The research method used is a descriptive method of analysis using path analysis. The results of this study are as follows: there is an effect of teacher competence (X1) on teacher performance (Y) with a total influence of 32.8%. Character values (X2) on teacher performance (Y) with an overall influence of 30.47%. There is an effect of teacher competence (X1), and character values (X2), simultaneously on teacher performance (Y) with a total influence of 63.3%. And the remaining 36.7% is a variable that is not examined in this study that affects teacher performance; 6) there is an effect of teacher performance (Y) on children's learning outcomes (Z) of 67.7%. And the remaining 32.3% is a variable that is not examined in this study that affects children's learning outcomes. This study concludes that it proves that there is an influence between teacher competence and character values on teacher performance and has implications for children's learning outcomes in elementary schools. Cileunyi District, Bandung Regency.